The Impact of Using Online Loans on the Consumptive Lifestyle of Students at the Sepuluh Nopember Institute of Technology, Surabaya - Danendra, Farel; Rahman, Muhammad Daffa Alvinoer; Erwada, Baringga Aurico De; Rakhmawati, Nur Aini (JURNAL SINTAK, 2024)
This research aims to analyze the impact of using online loans on the consumer lifestyle of students at the Sepuluh Nopember Institute of Technology (ITS) Surabaya. The research method used is quantitative through online surveys with purposive sampling data collection techniques. This research uses data from 53 respondents who are students at the Sepuluh Nopember Institute of Technology (ITS) Surabaya who are also online loan users. The research results show that ITS students who also use online loans tend to be consumptive and often buy goods without considering finances and needs just to improve their social status or because they are on sale. Consumptive behavior without considering needs and finances can have negative impacts in the long term, such as being in debt, having difficulty focusing on studies due to financial problems, and other problems in the future.